Al-Baqillani’s Critique to Rafidite Syi’ites’ on the Seven Variant Reading of The Qur’an - Much Hasan Darojat; Mohd. Fauzi Hamat; Wan Adli Wan Ramli (TSAQAFAH, 2016)
This article aims to delineate al-Baqillani’s response to the Rafidite Syi’ites’ claim on the invalidity of the variant readings of the Qur’an. As an Asy‘arite, al-Baqillani was able to disprove their claims dealing with the status of the variant readings of the Qur’an in the history of Islamic civilization. His arguments are also relevant to reject orientalists’s notion who are in line with those Syi’ites on the related topic. This issue has close relationship with the process of the compilation of the Qur’an and the validity of the Muṣḥaf of Utsman, since the Syi’ites rejected it and promoting their own version as claimed by their authoritative figures. The authors conclude that al-Baqillani’s defence on the matter provides number of evidence that the existing of the Qur’an is the one which was collected by Utsman ibn Affan. Al-Baqillani was also able to disprove the views that the variant readings of the Qur’an are merely ijtihâd and metaphorical statements. He clarified that the variant readings are valid and has been practiced by a number of companions and approved by the Prophet Muhammad, peace be upon him. His views on this issue were also supported by other scholars like al-Qurtubi and al-Zarqani. In this research, the approach that has been applied is textual analysis, using descriptive and analytical methods to investigate and analyze primary sources related to the pertinent topic. It also adopts the historical method to scrutinize several events on the subject within the context of the history of Islam.